1998
DOI: 10.1161/01.str.29.7.1305
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Hemispheric Activation in the Early Recovery of Motor Function After Stroke

Abstract: Background and Purpose-Functional recovery after cerebral infarction is a complex phenomenon that depends on various factors. The aim of this study was to investigate changes in cerebral perfusion during motor activity in stroke patients with very early recovery of motor function. Methods-We included 9 consecutive patients hospitalized for acute-onset hemiparesis who showed complete functional recovery within 24 hours. CT of the brain showed an ischemic or hemorrhagic cerebral lesion in areas compatible with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 28 publications
3
32
0
1
Order By: Relevance
“…Ipsilateral increases in blood flow velocity during movement of the paretic hand have been shown as early as 36 hours after stroke onset by transcranial Doppler. 20 Focal ipsilateral CBF increases have been shown in response to passive movement of a paretic limb 19 hours after stroke onset by positron emission tomography imaging. 21 One conclusion drawn from such data is that the role of the contralesional hemisphere is to provide ipsilateral motor pathways originating in the contralesional SMC.…”
Section: Discussionmentioning
confidence: 99%
“…Ipsilateral increases in blood flow velocity during movement of the paretic hand have been shown as early as 36 hours after stroke onset by transcranial Doppler. 20 Focal ipsilateral CBF increases have been shown in response to passive movement of a paretic limb 19 hours after stroke onset by positron emission tomography imaging. 21 One conclusion drawn from such data is that the role of the contralesional hemisphere is to provide ipsilateral motor pathways originating in the contralesional SMC.…”
Section: Discussionmentioning
confidence: 99%
“…We may propose TCD as a rapid and easy approach to furnish new information concerning brain responses when perturbing PPS. The understanding of CBF changes related to PPS perturbation can contribute to understanding the results of psychophysical and behavioral trials in either healthy or neurologic/neuropsychiatry conditions (e.g., poststroke neglect) (Cuadrado, Egido, Gonzalez‐Gutierrez, & Varela‐de‐Seijas, 1999; Halligan & Marshall, 1991; Holt et al., 2015; Riestra & Barrett, 2013; Silvestrini, Cupini, Placidi, Diomedi, & Bernardi, 1998). …”
Section: Discussionmentioning
confidence: 99%
“…The most plausible explanation for this phenomenon has been that there are uncrossed motor pathways accounting for approximately 25% of the fibers in the corticospinal tract of human beings and primates [9]. If these fibers have a role in the recovery of muscle strength [10, 11, 12], a second stroke affecting the contralateral hemisphere would not only produce a hemiparesis on the side contralateral to the new lesion, but also worsen the previous motor symptoms. Similarly, it has been shown that a considerable portion of the spinothalamic tract ascends ipsilaterally [13].…”
Section: Discussionmentioning
confidence: 99%